Impact of the Strategies Deployed by Morocco to Reduce Health and Socio-Economic Risks during the First Half of the COVID-19 Pandemic - Jossou, Thierry R.; MEDENOU, DATON (My University, 2021)
Abstract: Over the last three decades, the world has been confronted with several respiratory syndromes epidemics as: SARS in 2002, the H1N1 pandemic in 2009, the Middle East Respiratory Syndrome (MERS) in 2012 and the Ebola epidemic in 2014. They have resulted in significant direct and indirect mortality and morbidity. In this work, we analyze the strategies implemented by Morocco by highlighting the strengths and weaknesses of all the actions undertaken that have made Morocco an example in the COVID-19 pandemic management. In order to obtain convincing results, Morocco adopted the precautionary principle by taking drastic measures as soon as the first case of contamination appeared. These measures were taken considering the population, thus saving time and gradually acquiring the adequate logistical resources for the epidemic management. Among these measures which have proved their effectiveness, we find the emergence of a local sanitary equipment and devices industry necessary for the protection and care of COVID-19 (artificial respirator, masks, hydro-alcoholic gel...), the construction of the largest hospital in Africa in 15 days (700 beds) for the care of people with COVID-19, the chloroquine and hydroxychloroquine based dual therapy adoption, compensation for individuals and companies, the cultural aspect and societal practices in addition to strict progressive containment. Thus, the study of the strategies implemented by the government of the Kingdom of Morocco since the state of emergency declared on 20 March, the date of the containment beginning to its end, has highlighted the main influences on the capacity of all the players to successfully manage the socio-economic and health situation, making Morocco an example in the management of the COVID-19 pandemic, as have Germany, South Korea and the Scandinavian countries, with a lethality under 200 deaths.
Keywords: COVID-19; containment; Morocco; social; economic; health; disaster; management